E-wallet Adoption: Technology Acceptance Model and COVID-19 - Candy Candy; Shellyna Shellyna; Justyanita Justyanita; Kristiani Kristiani (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
The development of information technology has almost entered all economic and daily activities, such as in the financial aspect (financial technology). Since the pandemic, many e-wallets have been used as digital payment tools in Batam city, especially ShopeePay. Therefore, this study aims to analyze the level of adoption of ShopeePay by utilizing the TAM component and perceived risk, which refers to disease risk known as perceived COVID-19 risk. Purposive sampling is used as a sampling technique, with 179 samples obtained through google Forms filed by respondents. The results of this study found that there is a significant influence between perceived usefulness and ease of use on behavioral intention. Meanwhile, perceived COVID-19 risk does not significantly affect behavioral intention.